Conservation of Atlantic salmon by supplementary stocking of juvenile fish - Romakkaniemi, Atso (Helsingin yliopisto, 2010)
Wild salmon stocks in the northern Baltic rivers became endangered in the second half of the 20th century, mainly due to recruitment overfishing. As a result, supplementary stocking was widely practised, and supplementation of the Tornionjoki salmon stock took place over a 25 year period until 2002. The stock has been closely monitored by electrofishing, smolt trapping, mark-recapture studies, catch samples and catch surveys. Background information on hatchery-reared stocked juveniles was also collected for this study. Bayesian statistics was applied to the data as this method offers the possibility of bringing prior information into the analysis and an advanced ability for incorporating uncertainty, and also provides probabilities for a multitude of hypotheses. Substantial divergences between reared and wild Tornionjoki salmon were identified in both demographic and phenological characteristics. The divergences tended to be larger the longer the duration spent in hatchery and the more favourable the hatchery conditions were for fast growth. Differences in environment likely induced most of the divergences, but selection of brood fish might have resulted in genotypic divergence in maturation age of reared salmon. Survival of stocked 1-year old juveniles to smolt varied from about 10% to about 25%. Stocking on the lower reach of the river seemed to decrease survival, and the negative effect of stocking volume on survival raises the concern of possible similar effects on the extant wild population. Post-smolt survival of wild Tornionjoki smolts was on average two times higher than that of smolts stocked as parr and 2.5 times higher than that of stocked smolts. Smolts of different groups showed synchronous variation and similar long-term survival trends. Both groups of reared salmon were more vulnerable to offshore driftnet and coastal trapnet fishing than wild salmon. Average survival from smolt to spawners of wild salmon was 2.8 times higher than that of salmon stocked as parr and 3.3 times higher than that of ...